2014
DOI: 10.1519/jsc.0b013e3182a16d73
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Maximal and Explosive Strength Training in Recreational Endurance Runners

Abstract: Supervised periodized mixed maximal and explosive strength training added to endurance training in recreational endurance runners was examined during an 8-week intervention preceded by an 8-week preparatory strength training period. Thirty-four subjects (21-45 years) were divided into experimental groups: men (M, n = 9), women (W, n = 9), and control groups: men (MC, n = 7), women (WC, n = 9). The experimental groups performed mixed maximal and explosive exercises, whereas control subjects performed circuit tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 34 publications
1
42
0
2
Order By: Relevance
“…Some fluctuation was found, like in the combined endurance and strength training studies of Taipale et al. (2010; 2014) in recreational endurance runners, but it is possible that training should be more demanding for disturbing homeostasis of the hormonal system. Furthermore, according to these findings, it seems that basal testosterone and cortisol concentrations may not be sensitive enough for monitoring and predicting the adaptation to endurance training in recreational endurance runners.…”
Section: Discussionmentioning
confidence: 99%
“…Some fluctuation was found, like in the combined endurance and strength training studies of Taipale et al. (2010; 2014) in recreational endurance runners, but it is possible that training should be more demanding for disturbing homeostasis of the hormonal system. Furthermore, according to these findings, it seems that basal testosterone and cortisol concentrations may not be sensitive enough for monitoring and predicting the adaptation to endurance training in recreational endurance runners.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Taipale et al (2010) showed a positive effect of strength training on the specific performance of endurance athletes. Improvements in peak running speed have also been reported after mixed maximal and explosive strength training performed concurrently with endurance training in recreational endurance runners ( Taipale et al, 2014 ).…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, Deason et al (1991) found a significant relationship between 800 and 300 m running times. Other studies have also investigated the effects of strength-power training on middle and long-distance running performance ( Mikkola et al, 2011 ; Taipale et al, 2010 , 2014 ). For instance, Mikkola et al (2011) reported that both heavy and explosive resistance training programs were able to improve maximal endurance capacity in long-distance runners.…”
Section: Introductionmentioning
confidence: 99%
“…Em estudo com corredores recreativos dos sexos feminino e masculino, Taipale et al (2014) realizaram protocolos de treinamento de força rápida e força máxima com pequena frequência semanal, juntamente com o treinamento da corrida, para verificar se a aplicação do treino muscular superaria a realização do treino da corrida, somente, ou se afetaria negativamente o desempenho dos atletas, ao se instalar o fenômeno da interferência. Eles encontraram, no grupo que realizou treinamento contra resistência, aumentos significativos nas variáveis relativas à força máxima e ativação muscular, bem como naquelas relacionadas à capacidade aeróbia, como o limiar de lactato e a frequência cardíaca, concluindo que a aplicação do treinamento muscular de força máxima/rápida é bastante benéfica na melhoria do desempenho de corredores de ambos os sexos.…”
Section: Treinamento De Força Para Atletas De Provas Longasunclassified
“…Os testes de repetição máxima ou de contrações isométricas máximas são utilizados para verificar a capacidade contrátil de grupamentos musculares específicos em um dado exercício ou movimento, bem como fornecer índices de taxa de desenvolvimento de força (NUMMELA et al, 2008;MIKKOLA et al, 2011;TAIPALE et al, 2014VIKMOEN et al, 2016, e costumeiramente são realizados em aparelhos de treinamento de força, com cargas livres e sem auxílio de guias ou em equipamentos específicos, como dinamômetros isocinéticos ou de deformação estrutural (células de carga e afins) (MIDGLEY; McNAUGHTON;JONES, 2007;TAIPALE et al, 2013) O treinamento pliométrico, que é baseado essencialmente em saltos, tem se mostrado eficiente para o aumento de variáveis neuromusculares de potência e altura de saltos (RAMIREZ-CAMPILLO et al, 2014;CHELLY;HERMASSI;SHEPHARD, 2015;ACHE-DIAS et al, 2016). Em estudo com atletas de corrida, Chelly, Hermassi e Shephard (2015) identificaram que o treinamento pliométrico de dez semanas, aplicado em duas sessões semanais aumentou o desempenho para a altura de salto (SJ, CMJ e DJ) e reduziu o tempo de sprint (40m) quando comparado aos resultados do grupo controle, que apenas realizou suas sessões habituais de treinamento de corrida.…”
Section: As Técnicas De Saltos (Vertical -Squat Jump [Sj] Counter Mounclassified